Réponses

2013-05-14T17:38:22+02:00
2013-05-14T18:04:02+02:00

a) Dévolopper C et réduire :

 

C =(2x - 1) (3x+5) - (2x-1)

C = 6x² +5x -3x -5 -(4x²-4x +1)

C = 6x² +2x -5 -4x² +4x -1

C =2x²+6x -6

 

b) Factoriser C:

 

C =(2x - 1) (3x+5) - (2x-1)

C = (2x -1 ) (3x +5 -2x +1)

C = (2x -1) ( x +6)

 

 

 c) Résoudre l'équation C

 

 

2x -1 =0

 

x = 1/2

 

 

x + 6 =0

x = -6

 

Pour x = 2 et x = V2

 

 ( 2x2 -1) (2+6) = 24

 

( 2V2 -1) (V2+6)=  4+ 12V2 -1V2 -6 = -2 +11V2

 

 

2)Mettre sous la forme V6

 

 

B = 2V24 + V54

B = 2V6x V4 + V6 x V9

B = 4V6 + 3V6

B = 7V6